PKM MENGGALI POTENSI PEMANFAATAN LIMBAH CANGKANG KERANG MENJADI PUPUK DAN PAKAN SEBAGAI PENAMBAHAN NILAI EKONOMIS DI PULAU PASARAN KELURAHAN KOTA KARANG KECAMATAN TELUK BETUNG TIMUR KOTA BANDAR LAMPUNG - Euis Mufahamah; Anita Anita; Adi Prastyo; Andika Saputra; Rizkia Salsafara (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service program aims to explore the potential of utilizing shellfish waste on Pasaran Island, Kota Karang Village, Teluk Betung Timur District, Bandar Lampung City as a basic material for fertilizer and feed. Shellfish waste, which has not been optimally utilized, contains minerals that are useful for increasing soil fertility and as a source of protein in animal feed. The community service method includes waste collection, processing into organic fertilizer and additional feed, and the use of technology in processing shellfish waste. The stages in this activity are socialization, training, technology application, mentoring and evaluation, and program sustainability. The results of the community service program show that the utilization of shellfish waste can increase economic value while reducing environmental waste on Pasaran Island, Kota Karang, Teluk Betung Timur District, Bandar Lampung City. This utilization model is expected to be a sustainable solution for waste management while supporting the local economic development of the Pasaran Island community.